大專階段智能障礙學生之學習及就業轉銜概況之研究 Academic and Workplace Transition for College Students With Intellectual Disabilities: An Exploratory Study - 胡心慈 Shin-Tzu Hu; 林奕廷 Yi-Ting Lin (National Taiwan Normal University, 2023)
本研究從支持的角度關心智能障礙學生在大專校院學習及就業轉銜狀況，採用質量混合之序列研究方式進行，分別於2018年與2019年對有智能障礙畢業生之48所大專校院資源教室輔導員進行調查，再對輔導過智能障礙生之輔導員、教授、職業重建人員及學生本人共26人進行訪談，瞭解其所提供之支持及學生在課業學習及就業轉銜上的狀況。研究資料在量的部分以描述統計之總和及百分比處理，質的部分以恆常比較法歸納訪談資料以形成主題。研究結果分別從學校之支持、智能障礙生之學習及就業轉銜狀況談起，發現大部分學校並未特別做準備即招收智能障礙生，但仍會透過各種會議宣導、加強相關單位間之聯繫以提供教師與學生支持；資源教室提供學生課業學習及轉銜輔導上各種支持服務，但學生使用率並不高；任課教授願意利用個人時間個別輔導學生並使用多種教學調整策略，但學生理解力不足，輔 導成效有限；有些校外之職業重建人員在學生尚未畢業即已開始入校輔導。學生雖覺得課業學習很辛苦，但仍肯定大學生活能擴展視野，有47%的就業率。研究者最後擴充支持系統從生態系統理論之微系統、中介系統、外部系統及大系統分別進行討論並提出建議。 Purpose This study aimed to understand the challenges that students with intellectual disabilities encounter in the academic learning and adoption processes, and to explore the crucial support systems provided for students with intellectual disabilities by universities. Literature Review In Taiwan, most students with intellectual disabilities attend vocational high school and seek to work after graduating. However, the majority of students with mild and moderate intellectual disabilities attend university due to parental expectations and the greater number of opportunities offered by a higher education degree. Beginning in 1999, educational institutions began to establish resource rooms to support students with disabilities in Taiwan. However, research has indicated that students with intellectual disabilities require a high level of support in many aspects of life, particularly with regard to academic learning and adjustment, and few studies have explored how to best support these individuals. In the United States, postsecondary education programs designed to meet the needs of students with intellectual disabilities have one of three modes: (1) isolation mode, (2) hybrid mode, and (3) integrated individual support mode. Method This mixed methods study was conducted between 2018 and 2019. In the first stage, researchers designed questionnaires to investigate the support systems for and transition process of students at higher education institutions or in job hunting activities. The surveys were sent to 161 student disability service counselors in university resource rooms, with 48 questionnaires completed and returned. In the second stage, researchers individually interviewed student disability service counselors, professors, and rehabilitation case managers who had worked with students with intellectual disabilities. This study sought to assess how the abovementioned professionals supported students and how transition services were used in both academic and employment activities. In the third stage, interviewing student disability service counselors by conducting focus group. Results According to the findings, although most universities lacked specific preparation for students with intellectual disabilities, they strove to enhance the quality and frequency of communication between departments and the administration in an effort to provide support at the time of enrollment. However, the student utilization rate of disability services remained less than 20%, which included support services for academic learning, career counseling, and transition activities. Although students with intellectual disabilities highlighted the challenges of academic study, most still believed that the university experience would be beneficial. The majority of students with intellectual disabilities graduated from university on time with a 47% employment rate. Discussion This study expanded the current perspective on support systems by constructing a framework that encompasses the microsystem, mesosystem, exosystem, and macrosystem. The key actors in the microsystem were the parents, classmates, and professors of the students with intellectual disabilities. They were key in the students' adjustment to university life. In the mesosystem, student disability service counselors coordinated department offices and administration to construct a support system in universities. The resource room functioned as a safe space for students with intellectual disabilities. In the exosystem, some student disability service counselors connected students with job hunting resources before graduation; rehabilitation case managers and employers played large roles in the lives of graduates with intellectual disabilities. Many participants in the exosystem believed that obtaining a diploma was the paramount objective for students with intellectual disabilities who attend university; they hoped that a diploma would equip students with the self-determination to choose a career and expand their options. Conclusion 1. Students with intellectual disabilities confronted considerable challenges in academic learning, adjustment, and transition in university. 2. Students with intellectual disabilities did not receive adequate preparation before entering university. 3. Although student disability service counselors, professors, and rehabilitation case managers provided some support, few services were adopted. 4. Most students with intellectual disabilities graduated from university on time with a 47% employment rate. Suggestions This study adopted ecosystem theory to describe the support systems available to students with intellectual disabilities. 1. Providing curricular adjustments in higher education. This entails redesigning the course map, adjusting teaching strategies, and empowering professors to teach students with intellectual disabilities. In addition, administrators should provide transition services in a timely manner. 2. Developing a wider variety of postsecondary programs to expand options for students with intellectual disabilities. Students with intellectual disabilities in Taiwan must choose between joining the workforce or enrolling in higher education. Many US studies have noted that students with intellectual disabilities who participate in postsecondary programs exhibit improved academic performance, enhanced social and job-related skills, and a higher employment rate, self-determination, and quality of life. Students with intellectual disabilities will benefit considerably from the development of a wider variety of postsecondary programs providing extensive options based on student needs and career plans. 3. Doing away with the fixation on paper qualifications. Existing social norms place much value on a college degree, and parents and students chase after a degree just for the prestige. Changing mindsets and norms will be an uphill task. 4. For future studies: So far, domestic literature on the issue of students with intellectual disabilities attending university is still insufficient, and most of them are case studies. It's hard to see the whole picture. Future studies should focus on investigating the quality of life of students with intellectual disabilities after graduating from university.